Implementasi Undang-undang No 6 Tahun 2014 tentang Desa Rancasenggang, Kecamatan Sindangkerta, Kabupaten Bandung Barat (Sosialiasi, Hambatan, dan Dampaknya) - Deden Suhendar (Universitas Jenderal Ahmad Yani, 2019)
Good governance has been an important discourse in the development administration and democracy studies during the last two decades. The socialization process of Uu No. 6 of 2014 concerning Villages in Rancasenggang Village, Sindangkerta Subdistrict, West Bandung Regency, was carried out through a village law socialization program held by the Sindangkerta Subdistrict government, West Bandung Regency simultaneously with the village apparatus in all Sindangkerta Subdistrict, West Bandung Regency. The obstacles experienced by village officials and the community in the implementation of the Village Law in Rancasenggang Village, Sindangkerta Subdistrict, West Bandung Regency, are the existence of multi-interpretation regulations that burden the village government and Sindangkerta District government, West Bandung District in distributing village funds. The village apparatus in the implementation of the village law in the Rancasenggang Village Sindangkerta Subdistrict, West Bandung Regency, basically has understood the contents of the village law but has not been maximized because the socialization of the new village law was carried out once by the Sindangkerta District government, West Bandung Regency.